Challenges and Opportunities in Implementing a Halal Lifestyle: A Study of Global Halal Regulations - Khotibul Umam; Dyah Purbaningrum; Iklim Matunasia Aci (MONETARIUM: Journal of Economics Business and Management, 2024)
The halal lifestyle is increasingly becoming a global concern within Muslim societies and beyond. This creates significant challenges and opportunities in implementing halal regulations at the global level. This research aims to analyze halal regulations that apply globally, explore the main challenges faced in implementing them, and identify opportunities related to the development of a halal lifestyle. In this research, we conducted a comprehensive literature review of global halal regulations covering various aspects. We also explore emerging challenges, such as harmonization of standards, certification costs, and monitoring of halal products. In addition, we identify opportunities in developing the halal product industry, including global market expansion and product innovation. The results of this research illustrate the complexity in implementing halal regulations at the global level and highlight the need for coordination efforts between countries and collaboration between stakeholders. The challenge of harmonizing halal standards is also a major focus, with the expansion of the global market and increasing consumer awareness about halal. On the other hand, opportunities in developing the halal product industry are wide open with significant market growth potential. This research contributes to the understanding of global halal regulations and provides valuable insights for governments, producers and other stakeholders in facing challenges and exploiting opportunities in implementing a halal lifestyle at the global level.